Relevansi Nilai-Nilai Kearifan Lokal Kirab Sesaji di Desa Wonosari Gunung Kawi pada Pembelajaran Sejarah Kurikulum merdeka - Maharani, Ratih; Jauhari, Najib (Cetta: Jurnal Ilmu Pendidikan, 2024)
One thing that is no less important in studying history is preserving local wisdom so that future generations will know regional culture and develop positive attitudes that are reflected in these cultural traditions. Problems that can arise as a result of developments in increasingly modern times are generations of people who ignore local wisdom and this results in the erosion of the values ​​contained in local wisdom traditions. Therefore, the Independent Curriculum is present in history learning by creating new content, namely the integration of material regarding local wisdom. Kirab Sesaji is one of the local wisdoms in Wonosari Village, Gunung Kawi and contains many local wisdom values. The purpose of writing this research is to (1.) Outline the local wisdom content of history learning in the Merdeka Curriculum; (2). Explain the meaning of Kirab Sesaji tradition, and; (3). Find out the relevance of the local wisdom values ​​of the Carnival of Offerings in the history learning of the Merdeka Curriculum. The research method used is a qualitative method with literature studies and interviews. The data collected came from primary sources, namely oral interviews with the resource person Suwito as the head of Wonosari village, and secondary sources using literature studies such as exploration of journals, books and other library sources to support writing. The results of the research concluded that Kirab Sesaji contains local wisdom values ​​in the form of religious values, cultural values, social values ​​and educational values ​​that are relevant to the profile of Pancasila students studying history in the Merdeka Curriculum. The traditions and values ​​of Local Wisdom contained in the Kirab Sesaji also have relevance to the history learning phase E class X regarding the material coverage of the Islamic Kingdom in Indonesia.